2011
DOI: 10.1111/j.1365-2664.2011.01991.x
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of weed risk assessments for biofuels using Camelina sativa as a model species

Abstract: Summary1. Biofuel production has the potential of reducing CO 2 emissions while decreasing global dependence on fossil fuels. However, concerns have been raised on the invasiveness of biofuel feedstocks. Estimating invasion potential remains a challenge because of inconsistencies and inherent limitations of using first-tier qualitative weed risk assessment (WRA) protocols singularly. 2. We evaluated the usefulness of second-tier quantitative WRA methods using a recently introduced oilseed crop, Camelina sativa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In addition, it has been demonstrated that camelina has negligible potential as an invasive weed if grown in a large scale as biodiesel crop. 53 Studies have shown that camelina oil is a good feed stock for biodiesel (prepared via transesterification) production 54,55 and as a renewable jet fuel through hydrodeoxygenation/hydro cracking. 51 In the US, several companies including Accelergy Corp., Altair, Inc., Biojet Corp. and sustainable Oils, LLC have successfully produced camelina-derived jet fuel.…”
Section: Potential Uses and Industrial Applications For Camelinamentioning
confidence: 99%
“…In addition, it has been demonstrated that camelina has negligible potential as an invasive weed if grown in a large scale as biodiesel crop. 53 Studies have shown that camelina oil is a good feed stock for biodiesel (prepared via transesterification) production 54,55 and as a renewable jet fuel through hydrodeoxygenation/hydro cracking. 51 In the US, several companies including Accelergy Corp., Altair, Inc., Biojet Corp. and sustainable Oils, LLC have successfully produced camelina-derived jet fuel.…”
Section: Potential Uses and Industrial Applications For Camelinamentioning
confidence: 99%
“…To date, this has been accomplished on a limited spatiotemporal scale for a single oilseed crop ( Camelina sativa ) in the intermountain West of the USA (Davis et al . ). Here, we expand upon this approach using a spatial demographic model describing the population growth and spread of the herbaceous perennial bioenergy crop M .…”
Section: Introductionmentioning
confidence: 97%
“…Camelina sativa L. Cranz, a member of family Brassicaceae, is a relative of the genetic model organism Arabidopsis thaliana, which has gained increased popularity for its potential in biofuel applications (Fröhlich and Rice, 2005;Davis et al, 2011). C. sativa has been cultivated for oil production since prehistoric times and is widely distributed on marginal land (Imbrea et al, 2011).…”
Section: Introductionmentioning
confidence: 99%